2019
DOI: 10.1371/journal.ppat.1007964
|View full text |Cite
|
Sign up to set email alerts
|

Members of chitin synthase family in Metarhizium acridum differentially affect fungal growth, stress tolerances, cell wall integrity and virulence

Abstract: Chitin is an important component of the fungal cell wall with a family of chitin synthases mediating its synthesis. Here, we report on the genetic characterization of the full suite of seven chitin synthases ( MaChsI-VII ) identified in the insect pathogenic fungus, Metarhizium acridum . Aberrant distribution of chitin was most evident in targeted gene knockouts of MaChsV and MaChsVII . Mutants of MaChsI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 95 publications
6
42
0
Order By: Relevance
“…During normal growth, chitin biosynthesis genes like chitin synthases (CHS) and endochitinases [ 37 ] are needed for hyphal development and maintenance of cell wall integrity in fungi [ 38 ]. The observed up-regulation of CHS and endochitinases suggests that the fungus is growing and increasing in biomass during the interaction.…”
Section: Discussionmentioning
confidence: 99%
“…During normal growth, chitin biosynthesis genes like chitin synthases (CHS) and endochitinases [ 37 ] are needed for hyphal development and maintenance of cell wall integrity in fungi [ 38 ]. The observed up-regulation of CHS and endochitinases suggests that the fungus is growing and increasing in biomass during the interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Chitin is synthesized by chitin synthases and is crucial to the fungal cell wall integrity [ 63 ]. Studies have shown that ChsIII , ChsV , ChsVI and ChsVII affect the synthesis of polysaccharide in the cell wall, and ChsIII , ChsV and ChsVII are necessary for the cell wall integrity in M. acridum [ 36 ]. In addition, chitin syn synthases in A. fumigatus [ 64 ] and Botrytis cinerea [ 65 ] also affect the cell wall integrity.…”
Section: Discussionmentioning
confidence: 99%
“…The cell wall contents, chitin, β-1,3-glucan and mannoproteins, of M. acridum were determined according to the previous study [ 36 ]. Briefly, hyphae of the WT, Δ MaAreB and CP strains were respectively inoculated in a 40 mL 1/4SDY liquid medium (1/4 SDAY without agar) and cultured at 28 °C with 220 rpm for 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…In filamentous fungi, the chitin synthase was reported to be responsible for the synthesis of chitin [64]. In S. cerevisiae [65], Metarhizium acridum [66], Fusarium graminearum [67], and B. cinerea [68] chitin synthase are required for cell-wall integrity. In this study, we identified seven chitin synthases CgChs1-CgChs7 (Protein IDs: 1900258, 361644, 1836492, 1744167, 1830816, 1462050, and 30251, respectively) in C. gloeosporioides, and qRT-PCR was applied to determine the relative expression levels of these genes in WT and ∆CgEnd3.…”
Section: Cgend3 Is Required For Cell Wall Integritymentioning
confidence: 99%